2021
DOI: 10.1016/j.heliyon.2021.e05910
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Menosan® Salvia officinalis in the treatment of a wide spectrum of menopausal complaints. A double-blind, randomized, placebo-controlled, clinical trial

Abstract: To evaluate efficacy and safety of fresh Salvia officinalis extract tablets in relieving typical symptoms in menopausal women and to gain insight in the mode of action by measuring altered cerebral wave intensities. Methods: Randomized 80 menopausal women from 48-65 years of age received Menosan ® tablets [3 0 400 mg ethanolic extract of freshly harvested Salvia officinalis L.] or placebo under double-blind conditions for 4 weeks. An efficacy analysis evaluated the developments of the menopausal rating scale [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In fact, the community S. officinalis monograph established that the amount of thujone must be specified in a product and the daily exposure must be below 6.0 mg [ 45 ]. Also, in clinical trials, the bioactivity of product M was demonstrated despite thujone depletion in the tested product [ 15 , 23 ]. Due to these safety and efficacy aspects, free-thujone products should be preferred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the community S. officinalis monograph established that the amount of thujone must be specified in a product and the daily exposure must be below 6.0 mg [ 45 ]. Also, in clinical trials, the bioactivity of product M was demonstrated despite thujone depletion in the tested product [ 15 , 23 ]. Due to these safety and efficacy aspects, free-thujone products should be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms of action of S. officinalis have been reported [ 16 ]. Clinical studies on the treatment of menopausal symptoms demonstrate that S. officinalis improves not only vasomotor symptoms but also exerts a positive impact on somato-vegetative and psychological symptoms, thus addressing a wide range of menopausal disorders [ 15 , 23 ]. The results of a double-blind study on a group of 80 menopausal women randomized to receive tablets of 3400 mg of ethanol extract of S. officinalis or a placebo for 4 weeks showed the effect of S. officinalis on the restoration of unbalanced brain waves [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some postmenopausal women are less concerned about their symptoms, which can affect quality of life and the outcome of herbal remedies 41 . The efficacy of Salvia officinalis extract on menopausal symptoms has been reported in several studies but has been limited to menopausal anxiety studies [42][43][44] . The effectiveness of Salvia officinalis extract on menopausal symptoms has been reported in several studies but has been limited to menopausal anxiety studies.…”
Section: Discussionmentioning
confidence: 99%
“…β 1 wave shows that the human brain is in a thinking state [17]. β 2 shows that the brain is alert and excited [18]. If the athlete's β waveform fluctuates significantly, the excitability of the athlete's central nervous system gets stronger, his speed and intensity of nerve are strengthened, and his stress ability is improved, forming an excellent state to win in the competition.…”
Section: Eegmentioning
confidence: 99%